Correlation Between Allergy History in Family and Allergy Manifestation in School Age Children - Fitria Mahrunnisa; Sumadiono Sumadiono; Sri Mulatsih (The Avicenna Medical Journal, 2021)
Background: Asthma, eczema and allergic rhinitis are influenced by both genetic factor and environtment factors. Based on family history of allergy, allergic trace cards can identify the level of allergic risk in children. The relationship between family history of allergy and manifestation of allergic disease as a single allergy disease and allergic multimorbidity still need to be explored. The objective of this study was to identify the associations between family history of allergic disease and manifestation of allergic disease in school-age children.Methods: We conducted a cross sectional study on school age children with 6-13 years old at eight elementary schools in Yogyakarta. Family history of allergy was defined as reported asthma, eczema and allergic rhinitis in a parent or sibling and classified the level of allergic risk based on allergic trace cards. Subjects were questioned by standardized ISAAC questionnaire. The relationship between the two was analyzed by the Chi-squared analysis to assess the prevalence ratio (PR).Results: A total of 272 children with an average age of 8.4 years, allergic manifestations occurred more as multimorbidity (53%) with the highest incidence of RA+asthma (9%) compared with one allergic disease (47%) with the highest incidence of RA (11%). There was a significant relationship between family history of allergy and all manifestations of allergic disease with an increased risk of developing allergies by 3.3 (PR 3.3; 95% CI 2.3-4.8) and 2.8 times (PR 2.8; IK95% 1.8-4.3) in the moderate and high-risk score group. Asthma, RA and DA have a risk for coexistence with 2 other diseases of 2.5 (RP 2.5 IK95%; 1.9-3), 2.25 (PR 2.25 IK95%; 1.7 -3) and 1.9 times (PR 2.5 IK95%; 1.45-2.4).Conclusion: Family history of allergic disease is a risk factors for the development of allergic manifestation both a single allergic disease and multimobidity.